Antoñeta and Marta: Two new self-compatible late flowering almond cultivars - Egea J.; Dicenta F.; Berenguer T. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Two new self-compatible late-flowering almond cultivars released at CEBAS-CSIC (Spain) are presented. Both cultivars, obtained from the cross Ferragnès ¥ Tuono made in 1985, show the following characteristics: besides their self-compatibility (with a high degree of autogamy) and late-flowering, both cultivars have high productivity and more frost resistance than other late-flowering cultivars; the fruit of both cultivars have attractive, non-double, good flavoured kernels, with hard-shells and a percentage of kernel of around 35 per cent (Antoñeta) and 32 per cent (Marta). While Antoñeta shows a half-opened mid-branched habit, Marta is upright and low branched.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)